Design of Vacuum Packaging Tools to Increase the Resistance of Processed Cook Fish Products - Brilliant Mahardika; Eka Andriani (Bulletin of Culinary Art and Hospitality, 2022)
Processed snakehead fish product is a fishery product that is prone to decay during storage for a certain time. One of the efforts to inhibit the rotting of processed snakehead fish products in the form of nuggets is by packaging using a vacuum machine. Therefore, in this study will carry out the design of a vacuum machine. The design of this vacuum and packaging machine is carried out for the purpose of extending its service life and increasing the selling value of processed snakehead fish nugget products. The machine to be designed is expected to be capable of packaging in a short time and at an affordable price. This machine has several parts, for example, vacuum motor, vacuum clamp, body frame, and impulse sealer. The machine to be made has dimensions of 700mm (height) × 700mm (length) × 500mm (width) using an Arashi Ais type impulse sealer with a size of 40cm and the vacuum motor used is the V115N 2 CFM type. This vacuum machine is equipped with an on/off switch in the vacuum clamp section whose main function is to connect and break the electric current that enters the vacuum motor so that the vacuum motor will immediately start and stop. How to operate this vacuum machine is very easy, as easy as inserting a plastic package containing snakehead fish products into the sealer and clamping the vacuum clamp at the end of the package. This vacuum machine is equipped with an on/off switch in the vacuum clamp section whose main function is to connect and break the electric current that enters the vacuum motor so that the vacuum motor will immediately start and stop. How to operate this vacuum machine is very easy, as easy as inserting a plastic package containing snakehead fish products into the sealer and clamping the vacuum clamp at the end of the package. This vacuum machine is equipped with an on/off switch in the vacuum clamp section whose main function is to connect and break the electric current that enters the vacuum motor so that the vacuum motor will immediately start and stop. How to operate this vacuum machine is very easy, as easy as inserting a plastic package containing snakehead fish products into the sealer and clamping the vacuum clamp at the end of the package.